Analysis of residential location of ICT sector employees in a liveable city: a case of Kuala Lumpur, Malaysia - Mohit, Mohammad Abdul; Adnan, Muaz (2013)
Employment and residential location are interconnected in urban areas. The residential land use within a city and its surrounding areas are highly influenced by the employment provision in the city. In order to understand the internal dynamics between location of employment and housing, it is important to identify and analyze the various factors which influence the residential location choice. Understanding of these factors is important to determine the future physical form of the cities, transport policies and other development policies. With the above background, this paper attempts to study the residential location choice of Information Technology and Communication (ICT) sector employees in Kuala Lumpur City. The study examines the various factors and the extent to which these factors influence the residential location. The study intends to provide an understanding of residential location factors of ICT sector employees in Kuala Lumpur and a basis for further empirical research. Findings from this are expected to assist in land use planning, housing and infrastructure policies formulation and also to provide a general idea of future housing demand for the private developers and other relevant agencies.